2013
DOI: 10.21608/jpp.2013.74492
|View full text |Cite
|
Sign up to set email alerts
|

HETEROSIS AND COMBINING ABILITY IN SOME COTTON CROSSES IN TWO DIFFERENT ENVIRONMENTS: 1- Yield and yield components traits

Abstract: Two experiments were carried out at Sakha Agriculture Research Station,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…Results indicated that the crosses Giza 96 × Karshenky, Giza 94 x Australy 13 and Australy 13 × Karshenky were significant desirable heterosis relative to mid and better-parent for yield traits under study, while, the crosses Giza 96 × Pima S7 and Giza 92 x Karshenky were significant desirable heterosis relative to mid and better-parent for fiber traits under study. These results were in harmony with those obtained by Karademir and Gençer (2010), Attia (2014), Al-Hibbiny (2015), El-Fesheikawy et al (2015), Sorour et al (2015), Salem (2016) and Said et al (2021). Table 6.…”
Section:  Heterosissupporting
confidence: 90%
“…Results indicated that the crosses Giza 96 × Karshenky, Giza 94 x Australy 13 and Australy 13 × Karshenky were significant desirable heterosis relative to mid and better-parent for yield traits under study, while, the crosses Giza 96 × Pima S7 and Giza 92 x Karshenky were significant desirable heterosis relative to mid and better-parent for fiber traits under study. These results were in harmony with those obtained by Karademir and Gençer (2010), Attia (2014), Al-Hibbiny (2015), El-Fesheikawy et al (2015), Sorour et al (2015), Salem (2016) and Said et al (2021). Table 6.…”
Section:  Heterosissupporting
confidence: 90%
“…The good x good GCA combination could be due to additive and additive types of gene action which is fixable on nature which had significant SCA effects for studied traits. Yahia [32]; Sorour et al [33], Chinchane et al [26] and Yehia and EL-Hashash [34]. This study suggested that information of GCA effects of parent should be considered along with SCA effects and presence performance of hybrid for predicting the value of any hybrid.…”
Section: Specific Combining Ability (Sca) Effectsmentioning
confidence: 81%
“…The parent (Giza 89 x Giza 86) was the best combiner for boll weight, while the parent (Giza 89 x Sea) was the best combiner for upper half mean. Sorour et al, (2013) found that the best general combiner for most of studied traits was parent (10229 x G. 86). Also the best general combiners for most of studied traits were crosses Hibbiny et al, (2019-a) noticed that the estimates of specific combining ability (SCA) effects for the crosses Giza 90 x Karshenky, Giza 95 x Pima S 7, Giza 92 x Karshenky and Giza 96 x Suvin were significant desirable SCA effects for some yield traits.…”
Section: • the Mean Performance Of Genotypesmentioning
confidence: 94%